IMPLEMENTASI BUDAYA KERJA DALAM MENINGKATKAN KEDISIPLINAN GURU DI MAS AL-WASHLIYAH NEGERI LAMA KEC. BILAH HILIR KAB. LABUHANBATU - Nasution, Siska Rapika; Chaniago, Nasrul Syakur; Rifa’I, Muhammad (Hijri, 2021)
This study aims to determine: (1) The work culture of teachers at MAS Al-Washliyah Negeri Lama, Kec. District Downstream Labuhanbatu, (2) Discipline of teachers at MAS Al-Washliyah Negeri Lama, Kec. District Downstream Labuhanbatu, (3) Supporting and inhibiting factors in implementing Work Culture in improving teacher discipline at MAS Al-Washliyah Negeri Lama, Kec. District Downstream Labuhanbatu. The method used in this research is qualitative to understand the phenomenology experienced by the research subjects in the form of observations, interviews and documentation with an emphasis on information data sources, namely: principals, teachers, and school committees to strengthen the validity of the data obtained. From the results of this study using 3 findings, namely: (1) The work culture of teachers at MAS Al-Washliyah Negeri Lama, Kec. District Downstream Labuhanbatu culture has communicated smoothly between teachers and principals. the work culture applied at MAS Al-Washliyah has been going well, and its implementation can be beneficial for both teachers and students, (2) Discipline of teachers at MAS Al-Washliyah Negeri Lama, Kec. District Downstream Labuhanbatu good discipline means that employees and teachers are aware and willing to do all their duties well. The principal realizes that the essence of leadership lies in a clear relationship between the leader, who is led and understands leadership as an activity to achieve group goals, (3) Supporting and inhibiting factors in the implementation of Work Culture in improving teacher discipline at MAS Al-Washliyah Negeri Lama, Kec. . District Downstream Labuhanbatu is the transportation used by teachers because the distance between the teacher's house and the school is far, causing the teacher's lack of discipline to arrive early before entering class, lack of funding for school administrators, and lack of school facilities.Work Culture, Teacher Discipline